Seroprevalence and risk factors of Toxoplasma gondii in cattle from Unai, Minas Gerais state, Brazil - Silva, Bruno Montijo; Queiroz, Willian Cristof Correia; Maia, Maerle Oliveira; Pacheco, Richard de Campos; Aguiar, Daniel Moura; Campos, Maíza Souza; Bresciani, Katia Denise Saraiva [UNESP]; Costa, Alvimar José [UNESP]; Gomes, Ana Amélia Domingues; Santos-Doni, Thais Rabelo (Elsevier, 2021)
Toxoplasma gondii is a widespread protozoan parasite that causes infections in animals and humans. The presence of tissue cysts in cattle musculature evidences their epidemiological significance in transmission to humans. The present study aimed to evaluate the seroprevalence of and risk factors of T. gondii seropositivity in beef cattle in the municipality of Unaí, Minas Gerais state, Brazil. Bovine blood samples (n = 612) were collected from 31 herds. Risk factors associated with the animal-level and herd-level seroprevalence were analysed using a questionnaire that investigates the epidemiological aspects of toxoplasmosis. A search for anti-T. gondii antibodies was performed by means of an indirect fluorescent antibody test (IFAT). Analysis of 612 samples showed 369 animals positive for anti-T. gondii antibodies (IFAT ≥64), with a seroprevalence of 60.29% (95% confidence interval (CI): 56.35–64.10). The herd-level seroprevalence was 96.77% (95% CI: 79.00–99.58). Applying a multivariate logistic regression analysis, a test of the association between seroprevalence of T. gondii infection and the potential predictors showed that cats (domestic or wild) with access to the drinking water of cattle were a significant (P = 0.001) predictor. The seroprevalence of T. gondii in cattle destined for human consumption is widely distributed throughout the entire study area. Thus, integrated control measures and strategies are suggested to prevent T. gondii infection in cattle.
Keywords: Brazil; Cattle; Risk factors; Seroprevalence; Toxoplasma gondii